Find the sum of all real solutions to the equation
2 cos x = 2 x + 2 − x .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Could you please explain???
Log in to reply
If x is a solution, then so is − x , so, the solutions add up to 0.
Those one liners of yours. Pfft. They kill the question.
These kinds of solutions are your best one-liners Sir. It reminds me of Solve for x . And, the good thing is that, inspired by your solution to that problem, this time even I solved it the same way.
Can you explain what is even function and the rest ?
Log in to reply
f ( x ) is said to be an even function if f ( − x ) = f ( x ) for all x . If a is a root of an even function, then so is − a since f ( − a ) = f ( a ) = 0 . Because of this symmetry, the sum of the roots is zero (provided that there are only finitely many roots).
Am I Right?
2 cos x =
2
x
+
2
−
x
Taking Log On Both Sides...............
log(2 cos x) = x log(2) - x log(2)
log(2 cos x) = 0
Since, log(1) = 0
2 cos x = 1
cos x = 1/2
Therefore, x = 0
Log in to reply
"Taking log on both sides" is flawed: lo g ( a + b ) = lo g ( a ) + lo g ( b ) in general
(The last step is flawed as well)
Solved Exactly the same way in about 5 seconds
By the AM-GM inequality we have that 2 x + 2 x 1 ≥ 2 2 x ∗ 2 x 1 = 2 ,
with equality holding when 2 x = 2 x 1 ⟹ 2 2 x = 1 ⟹ x = 0 .
Now for x ∈ R we have − 2 ≤ 2 cos ( x ) ≤ 2 , so the given equality holds only when both sides equal 2 , which only occurs when x = 0 .
Exact Same way... (+1)..
@Paola Ramírez Nice question. For sake of clarity I would suggest that the text of your question be "Find the sum of all real solutions to the equation 2 cos ( x ) = 2 x + 2 − x ".
Log in to reply
Thank you! I'll take your suggestion. Nice solution
2 x + 2 − x = e ln ( 2 ) x + e − ln ( 2 ) x = 2 cosh ( ln ( 2 ) ⋅ x )
cosh ( ln ( 2 ) ⋅ x ) = cos ( i ln ( 2 ) ⋅ x )
Now, we have cos ( x ) = cos ( i ln ( 2 ) ⋅ x ) and x = i ln ( 2 ) ⋅ x + k π
Because x is real, the only solution is 0
We can use the fact that, max & min values of cosx is -1 & 1 (for real x) and also in our case, cosx can't take negative values which makes the problem more simple!
Problem Loading...
Note Loading...
Set Loading...
My favourite technique: LHS and RHS are both even functions so that the answer is 0 by symmetry